Negative electrode material and preparation method and application thereof
By forming a composite cladding layer on the graphite and hard carbon composite negative electrode material of electric vehicle batteries, the lithium embedding capability and transmission speed of lithium ions are improved, and the problems of slow charging speed and lithium evolution in electric vehicles are solved, achieving efficient fast charging and long-lived battery performance.
Patent Information
- Application Number
- CN202411264258.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The charging speed of existing electric vehicles is slow, resulting in serious lithium-ion excision of lithium in graphite negative electrode materials, affecting the cycle life and safety performance of the battery. It is difficult for the existing technology to effectively improve the charging capacity under large-scale fast charging and discharging conditions. .
A composite of graphite and hard carbon is used as the matrix material, and a composite cladding layer is formed on its surface, including a first cladding layer of carbon material and conductive agent, and a second cladding layer of lithium-containing compound, by graphitization and carbonization The treatment enhances the porous structure and defects of the material to form efficient lithium embedded channels and high-speed channels.
It realizes the ability to fully charge 80% of the battery under 8-10C fast charging, reduces the lithium separation level, extends the battery's cycle life, and improves safety performance.
Smart Images

Figure CN119133404A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a negative electrode material and a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development and continuous popularization of electric vehicles, charging speed has become a concern for more and more car owners, and has also become the focus of technical research for many car companies. Fast charging has also become one of the most important measurement indicators in the field of electric vehicles.
[0003] Compared with traditional fuel vehicles, the biggest disadvantage of electric vehicles is the charging time. Therefore, if electric vehicles are to replace traditional fuel vehicles, charging speed is one of the key technologies that must be overcome. In the power battery system, the negative electrode material is the key to determining its charging speed. Under high-rate rapid charging and discharging conditions, if lithium ions do not have time to embed into the graphite layers of the negative electrode, the so-called lithium precipitation occurs. The precipitated lithium is easily deposited on the graphite surface to form lithium dendrites, which seriously affects the cycle life and safety performance of the battery. Therefore, it is particularly important to improve the charging capacity of the negative electrode material.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] An object of the present invention is to provide a negative electrode material having excellent fast charging capability and good cycle performance.
[0006] Another object of the present invention is to provide a method for preparing the negative electrode material, which has a simple process and low cost. The obtained negative electrode material has the characteristics of high initial efficiency and excellent kinetic performance, and can also have a long cycle life under high-rate rapid charging.
[0007] An object of the present invention is to provide a negative electrode sheet.
[0008] An object of the present invention is to provide a battery.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A negative electrode material comprises a base material and a composite coating layer coated on the surface of the base material, wherein the base material comprises a composite of graphite and hard carbon, and the base material has a porous structure, and the composite coating layer comprises a first coating layer coated on the surface of the base material and a second coating layer coated on the surface of the first coating layer, wherein the first coating layer comprises a carbon material and a conductive agent, and the second coating layer comprises a lithium-containing compound.
[0011] In some embodiments, the conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene and acetylene black.
[0012] In some embodiments, the lithium-containing compound includes at least one of lithium phosphate, lithium acrylate, and lithium sulfonate.
[0013] A method for preparing a negative electrode material comprises the following steps:
[0014] The mixture of pretreated raw coke and resin is granulated to obtain a first material, the first material is graphitized to obtain a second material, the mixture of the second material and alkali solution is pyrolyzed to obtain a matrix material; the mixture of the matrix material, a surface modifier and a conductive agent is carbonized to form a first coating layer, and a lithium compound solution is coated on the surface of the first coating layer, and a second coating layer is formed after drying to obtain a negative electrode material with a composite coating layer.
[0015] In some embodiments, the pretreated raw coke includes at least one of petroleum coke, needle coke and coal-based pitch coke.
[0016] In some implementations, the particle sizes D10, D50, and D90 of the pretreated raw coke satisfy: 1.1≤(D90-D10) / D50≤1.6.
[0017] In some embodiments, the pretreated raw coke is obtained by shaping and grading raw coke with a particle size D50 of 5 to 15 μm.
[0018] In some embodiments, the resin comprises a phenolic resin.
[0019] In some embodiments, the mass ratio of the pretreated raw coke to the resin is (85-95):(5-15);.
[0020] In some embodiments, the mixture of the pretreated raw coke and the resin is heat treated before being granulated.
[0021] In some embodiments, the granulation size of the first material is X=D2 / D1, wherein D2 is the particle size D50 of the first material after granulation, D1 is the particle size D50 before granulation, and X=1.2-2.
[0022] In some embodiments, the temperature of the graphitization treatment is 2000-3200° C., the heating time of the graphitization treatment is 40-50 hours, and the constant temperature time is 40-50 hours.
[0023] In some embodiments, after the graphitization treatment, the product is naturally cooled to 120-155° C. and then taken out of the furnace.
[0024] In some embodiments, the alkali solution includes at least one of a KOH solution and a NaOH solution.
[0025] In some implementations, the mass ratio of the second material to the alkali solution is (5-8):(2-5).
[0026] In some embodiments, the temperature of the pyrolysis treatment is 500-1000° C., and the time of the pyrolysis treatment is 1-4 hours.
[0027] In some embodiments, the pyrolysis treatment is performed under protective gas conditions.
[0028] In some embodiments, the surface modifier includes at least one of petroleum asphalt, coal asphalt, polymer materials, resins and biomass materials.
[0029] In some embodiments, the conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene and acetylene black.
[0030] In some embodiments, the lithium-containing compound includes at least one of lithium phosphate, lithium acrylate, and lithium sulfonate.
[0031] In some embodiments, the mass percentage of the lithium-containing compound in the lithium-containing compound solution is 5% to 15%.
[0032] In some embodiments, the mass ratio of the matrix material, the surface modifier, the conductive agent and the lithium-containing compound solution is (70-95):(3-10):(1-5):(1-5).
[0033] In some embodiments, the temperature of the carbonization treatment is 600 to 1900° C., and the time of the carbonization treatment is 48 to 72 hours.
[0034] In some embodiments, a preheating treatment is performed before the carbonization treatment, the temperature of the preheating treatment is 200 to 500° C., and the time of the preheating treatment is 5 to 8 hours.
[0035] In some embodiments, the drying temperature is 100-200°C.
[0036] In some embodiments, after the drying, the process further includes screening and demagnetization.
[0037] A negative electrode sheet comprises the negative electrode material or the negative electrode material prepared by the negative electrode material preparation method.
[0038] A battery comprises the negative electrode sheet.
[0039] An electrical device comprises the battery.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) In the negative electrode material of the present invention, the matrix material includes a composite of graphite and hard carbon, and has a rich porous structure and defects, which can increase the lithium insertion channel of lithium ions inside the particles and improve the fast charging capability; the composite coating layer formed by the carbon material, the conductive agent and the lithium-containing compound can effectively improve the defect interface conductivity and reduce the overall cross-linking impedance. In addition, by introducing the lithium-containing compound, the Li + The transport capacity between carbon layers can build a high-speed channel for Li, which can promote the Li + Removing solvents improves the fast charging performance of graphite; the negative electrode material can achieve 8-10C fast charging, which means it can be recharged to 80% of the capacity in 5-6 minutes.
[0042] (2) The preparation method of the negative electrode material of the present invention comprises granulating the mixture of raw coke and resin, which can improve the isotropy of the material and the charging capacity of the material; during the high-temperature pyrolysis process, the alkali solution activates the second material, and the gas generated during the reaction is conducive to the further formation of the pore structure, and the metal ions can enter the carbon skeleton, causing the carbon lattice to expand, thereby forming more micropores, and the bulk end face modification effect forms a relatively rich pore and defect surface, which can increase the lithium ion insertion channel inside the particle; by preparing a composite coating layer, a functionalized interface is realized. Modification and high-throughput particle conduction network construction, the specific advantages include: 1) The conductive agent can enhance the electron cloud density, improve the conductivity of the carbon material, and improve the lithium ion storage capacity; 2) Because electron transmission can only be carried out through the conjugated π bonds in the graphite layer, the conventional coating layer is rich in mesoporous coating layers or large defect graphite end faces. The electron transmission is blocked and the cross-linking impedance is large. The composite coating layer formed by the surface modifier, the conductive agent, and the lithium-containing compound in the present invention can effectively improve the defect interface conductivity and reduce the overall cross-linking impedance; 2) In addition, the introduction of polar lithium-containing compounds in the composite coating layer can improve Li + The transport capacity between carbon layers can build a high-speed channel for Li elements and promote the Li + Remove solvents and improve the fast charging performance of graphite; at the same time, the polarity of carbon surface increases the surface reaction activity of the material, more efficiently adsorbs foreign atoms, forms defect sites, and reduces Li + Mass transfer resistance.
[0043] (3) The battery of the present invention has excellent fast charging capability, low lithium plating degree, long cycle life and good safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0045] Figure 1 This is a scanning electron microscope image of the negative electrode material in Example 1 of the present invention;
[0046] Figure 2 This is a scanning electron microscope image of the negative electrode material in Example 2 of the present invention. DETAILED DESCRIPTION
[0047] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0048] According to one aspect of the present invention, the present invention relates to a negative electrode material, including a base material and a composite coating layer coated on the surface of the base material, the base material including a composite of graphite and hard carbon, the base material having a porous structure, the composite coating layer including a first coating layer coated on the surface of the base material and a second coating layer coated on the surface of the first coating layer, the first coating layer including a carbon material and a conductive agent, and the second coating layer including a lithium-containing compound.
[0049] In the negative electrode material of the present invention, the matrix material includes a composite of graphite and hard carbon, and the matrix material has a rich porous structure and defects, which increases the lithium insertion channel of lithium ions in the particles. The hard carbon can increase the disorder between particles, reduce the OI value, and improve the fast charging ability; the composite coating layer can effectively increase the defect interface conductivity and reduce the overall cross-linking impedance. In addition, by introducing a lithium-containing compound, the Li + The transport capacity between carbon layers can build a high-speed channel for Li, which can promote the Li + The solvent is removed to improve the fast charging performance of graphite. The negative electrode material can achieve 8-10C fast charging, which means that it can be recharged to 80% in 5-6 minutes.
[0050] In some embodiments, the conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene and acetylene black. The conductive agent can be selected from any one or a combination of the above, such as a combination of carbon black and conductive graphite, a combination of carbon fiber and carbon nanotube, a combination of carbon nanotube, graphene and acetylene black, etc.
[0051] In some embodiments, the lithium-containing compound includes at least one of lithium phosphate, lithium acrylate and lithium sulfonate, such as a combination of lithium phosphate and lithium acrylate, lithium acrylate and lithium sulfonate, and the like.
[0052] According to another aspect of the present invention, the present invention also relates to a method for preparing a negative electrode material, comprising the following steps:
[0053] The mixture of pretreated raw coke and resin is granulated to obtain a first material, the first material is graphitized to obtain a second material, the mixture of the second material and alkali solution is pyrolyzed to obtain a matrix material; the mixture of the matrix material, a surface modifier and a conductive agent is carbonized to form a first coating layer, and a lithium compound solution is coated on the surface of the first coating layer, and a second coating layer is formed after drying to obtain a negative electrode material with a composite coating layer.
[0054] The preparation method of the negative electrode material of the present invention granulates the mixture of raw coke and resin, which can improve the isotropy of the material and the charging capacity of the material. The resin is used as the granulation base, and the hard carbon formed by the resin under the high temperature of graphitization treatment is a highly unnecessary structure, which is not easy to graphitize at high temperature, and can increase the disorder between particles, reduce OI, and improve the fast charging of the material. During the high-temperature pyrolysis process, the alkali solution activates the second material, and the gas generated during the reaction is conducive to the further formation of the pore structure, and the metal ions can enter the carbon skeleton, so that the carbon lattice expands, thereby forming more micropores, and the bulk end face modification effect forms a relatively rich pore and defect on the surface, which can increase the lithium insertion channel of lithium ions inside the particles. Furthermore, a composite coating layer is prepared on the surface of the base material to achieve functional interface modification and high-flux particle conduction network construction. The specific advantages include: 1) The conductive agent can enhance the electron cloud density, improve the conductivity of the carbon material, and improve the lithium ion storage capacity; 2) Since electron transmission can only be carried out through the conjugated π bonds in the graphite layer, the conventional coating layer is rich in mesoporous coating layers or large defect graphite end faces. The electron transmission is hindered and the cross-linking impedance is large. The composite coating layer formed by the base material and the surface modifier, the conductive agent, and the lithium-containing compound in the present invention can effectively improve the defect interface conductivity and reduce the overall cross-linking impedance; 2) In addition, the polar lithium-containing compound is introduced into the composite coating layer to improve the Li + The transport capacity between carbon layers can build a high-speed channel for Li elements and promote the Li +Remove solvents and improve the fast charging performance of graphite; at the same time, the polarity of carbon surface increases the surface reaction activity of the material, more efficiently adsorbs foreign atoms, forms defect sites, and reduces Li + Mass transfer resistance.
[0055] In some embodiments, the pretreated raw coke includes at least one of petroleum coke, needle coke and coal-based pitch coke, such as a combination of petroleum coke and needle coke, a combination of needle coke and coal-based pitch coke, and the like.
[0056] In some embodiments, the pretreated raw coke is obtained by shaping and grading raw coke with a particle size D50 of 5 to 15 μm (e.g., 5 μm, 6 μm, 10 μm or 15 μm, etc.). The particle size D50 of the raw coke is preferably 5 to 10 μm. The smaller the particle size, the shorter the distance of lithium ion transmission inside the particle and the higher the kinetics. If the particle size is too small, the crushing yield is low and the cost is high, so the particle size needs to be controlled within a certain reasonable range.
[0057] In some embodiments, the particle sizes D10, D50, and D90 of the pretreated raw coke satisfy: 1.1≤(D90-D10) / D50≤1.6, and the values of (D90-D10) / D50 are, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, etc.
[0058] In some embodiments, the resin comprises a phenolic resin, preferably a thermoplastic phenolic resin.
[0059] In some embodiments, the mass ratio of the pretreated raw coke to the resin is (85-95):(5-15); for example, 85:15, 88:12, 90:10, 95:5, etc. The pretreated raw coke and the resin have a suitable mass ratio, thereby ensuring that the graphite and hard carbon material in the obtained second material have a suitable ratio to work in a coordinated manner.
[0060] In some embodiments, the mixture of raw coke and resin is subjected to heat treatment before granulation, that is, the raw coke and resin are directly granulated after being mixed or granulated after being heat treated.
[0061] In some embodiments, the granulation size of the first material is X=D2 / D1, wherein D2 is the particle size D50 of the first material after granulation, D1 is the particle size D50 before granulation, and X=1.2-2, such as 1.2, 1.3, 1.5, 1.6, 1.8 or 2. Granulation is used to improve the isotropy of the material and the charging capacity of the material.
[0062] In some embodiments, the temperature of the graphitization treatment is 2000-3200°C, including but not limited to 2000°C, 2100°C, 2200°C, 2300°C, 2500°C, 2600°C, 2700°C, 2800°C, 3000°C, 3200°C, etc., or any range between the two. In some embodiments, the heating time of the graphitization treatment is 40-50h, such as 40h, 45h, 50h, etc., and the constant temperature time is 40-50h, such as 40h, 45h, 48h or 50h, etc. After the graphitization treatment, it is naturally cooled to 120-155°C (such as 130°C, 140°C, 150°C, etc.) and taken out of the furnace.
[0063] In some embodiments, the graphitization treatment uses at least one of a box furnace, a crucible furnace, a continuous graphitization furnace, and an internal series furnace. Appropriate graphitization treatment conditions can form graphite from the pretreated raw coke, and the resin can form a highly undesirable hard carbon material, which can increase the disorder between particles, reduce OI, and improve the fast charging performance of the material.
[0064] In some embodiments, the alkaline solution includes at least one of a KOH solution and a NaOH solution.
[0065] In some embodiments, the mass ratio of the second material to the alkali solution is (5-8):(2-5), such as 5:2, 6:2.7, 7:4, 7.5:4.5 or 8:5, etc. The use of a suitable mass ratio of the second material to the alkali solution is more conducive to ensuring the activation effect of the alkali solution, so as to better perform bulk end face modification.
[0066] In some embodiments, the temperature of the pyrolysis treatment is 500-1000°C, including but not limited to 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, etc., or any range between the two. In some embodiments, the time of the pyrolysis treatment is 1-4h, such as 1h, 1.5h, 2h, 2.5h, 3h, 4h, etc. The pyrolysis treatment is carried out under protective gas conditions, such as nitrogen, argon, helium, etc. The present invention adopts suitable pyrolysis treatment conditions to enable the alkali solution to better activate the second material, so as to obtain suitable pores and defects, and increase the lithium insertion channels of lithium ions inside the particles.
[0067] In some embodiments, the surface modifier includes at least one of petroleum asphalt, coal asphalt, polymer materials, resins and biomass materials, such as a combination of petroleum asphalt and coal asphalt, a combination of petroleum asphalt, coal asphalt and resin, etc.
[0068] In some embodiments, the conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotubes, graphene and acetylene black, such as a combination of carbon black and conductive graphite, a combination of carbon fiber and carbon nanotubes, and the like.
[0069] In some embodiments, the lithium-containing compound includes at least one of lithium phosphate, lithium acrylate, and lithium sulfonate, such as a combination of lithium phosphate and lithium acrylate, a combination of lithium acrylate and lithium sulfonate, and the like.
[0070] In some embodiments, in the lithium-containing compound solution, the mass percentage of the lithium-containing compound is 5% to 15%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc.
[0071] In some embodiments, the mass ratio of the base material, the surface modifier, the conductive agent and the lithium-containing compound solution is (70-95): (3-10): (1-5): (1-5), for example, 70:3:1:1, 80:10:5:5, 85:8:3:4, 88:6:3:3, 90:8:1:1, 95:10:5:5, etc. The base material, the surface modifier, the conductive agent and the lithium-containing compound solution of the present invention adopt an appropriate mass ratio to ensure the interface modification effect of the obtained composite coating layer and the effect of building a high-throughput particle conduction network, which can effectively improve the defect interface conductivity, reduce the overall cross-linking impedance, and improve Li + The transport capacity between carbon layers promotes the Li + Remove solvent and improve the fast charging performance of graphite.
[0072] In some embodiments, the temperature of the carbonization treatment is 600-1900°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1500°C, 1800°C, 1900°C, etc., or any range between the two. The time of the carbonization treatment is 48-72h, such as 48h, 50h, 60h, 70h, etc.
[0073] In some embodiments, the carbonization treatment is preceded by a preheating treatment, the preheating treatment temperature is 200-500°C, for example, 200°C, 250°C, 300°C, 350°C, 400°C, 500°C, etc., and the preheating treatment time is 5-8h, for example, 5h, 5.5h, 6h, 7h or 8h, etc.
[0074] In some embodiments, the coating of the lithium compound solution is carried out by spraying through a spray drying device. In some embodiments, the drying temperature is 100-200°C, for example, 100°C, 120°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.
[0075] In some embodiments, after drying, the process further includes screening and demagnetization to obtain a negative electrode material with suitable particle size and high purity.
[0076] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet, comprising the negative electrode material, or the negative electrode material prepared by the negative electrode material preparation method.
[0077] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode layer located on at least one side surface of the negative electrode current collector, and the negative electrode layer comprises the above-mentioned negative electrode material, a conductive agent and a binder.
[0078] According to another aspect of the present invention, the present invention also relates to a battery comprising the above-mentioned negative electrode sheet.
[0079] The battery of the present invention has excellent fast charging capability and good cycle performance.
[0080] In some embodiments, the battery of the present invention includes a positive electrode sheet, the negative electrode sheet described above, a separator, and an electrolyte.
[0081] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the battery, such as an electric car, a portable device, and the like.
[0082] The following is further explained in conjunction with specific embodiments and comparative examples.
[0083] Example 1
[0084] A method for preparing a negative electrode material comprises the following steps:
[0085] (1) Raw material pulverization: The petroleum coke raw material was pulverized using a pulverizer to obtain particles with a D50 of 10 μm.
[0086] (2) Surface shaping and classification: The particles in step (1) are subjected to surface shaping and classification to adjust the particle size distribution of the material to: (D90-D10) / D50=1.3.
[0087] (3) Granulation: The pretreated raw coke shaped and classified in step (2) is mixed with a thermoplastic resin (granulating agent) and then granulated, and the granulation size X (D2 / D1) is controlled to be 1.3 to obtain a first material, wherein the mass ratio of the pretreated raw coke to the thermoplastic resin is 90:10.
[0088] (4) Graphitization: The material in step (3) is subjected to high-temperature graphitization treatment in a graphitization furnace at 3200° C. The graphitization temperature is raised to 3200° C. for 35 hours, kept at a constant temperature for 45 hours, then naturally cooled to 150° C., taken out of the furnace, and a second material is obtained.
[0089] (5) Bulk phase end face modification: The second material in step (4) is mixed with an alkali solution, wherein the alkali solution is a NaOH solution, and the mass ratio of the second material to the alkali solution (expressed as Q) is 6:4, and high-temperature pyrolysis is performed at 1000°C for 2h under the protection of a N2 atmosphere to obtain a matrix material.
[0090] (6) Functionalized interface modification and high-throughput particle conductive network construction: The matrix material obtained in step (5) is mixed with a surface modifier and a conductive agent, preheated at 300°C for 3 hours, and then carbonized at 1150°C in a carbonization furnace for 48 hours to form a first coating layer. The lithium compound solution is then spray-dried to coat the surface of the material at a drying temperature of 130°C to form a second coating layer, thereby obtaining a negative electrode material having a composite coating layer.
[0091] The mass ratio of the matrix material to the surface modifier, the conductive agent and the lithium-containing compound solution (expressed as R) is 90:5:2:3, the surface modifier is asphalt with a softening point of 180°C, the conductive agent is graphene, and the lithium-containing compound solution is a lithium sulfonate solution, wherein the mass percentage of lithium sulfonate is 8%.
[0092] (7) Screening and demagnetization: The material obtained in step (6) is screened and demagnetized to obtain the desired supercharged negative electrode active material.
[0093] The scanning electron microscope image of the negative electrode material in this embodiment is as follows Figure 1 shown.
[0094] Embodiments 2 to 15
[0095] The preparation methods of the negative electrode materials of Examples 2 to 15 differ from those of Example 1 in that the specific parameter conditions are different, see Table 1.
[0096] The mass ratio of the second material to the alkali solution is represented by Q.
[0097] The mass ratio of the base material to the surface modifier, the conductive agent and the lithium-containing compound solution is represented by R.
[0098] Table 1 Parameter conditions of Examples 2 to 15
[0099]
[0100]
[0101] Among them, the scanning electron microscope image of the negative electrode material in Example 2 is as follows Figure 2 shown.
[0102] Comparative Example 1
[0103] The method for preparing the negative electrode material comprises the following steps:
[0104] (1) Raw material pulverization: The petroleum coke was pulverized using a pulverizer to obtain particles with a D50 of 10 μm.
[0105] (2) Surface shaping and classification: The particles in step (1) are subjected to surface shaping and classification to adjust the particle size distribution of the material to 1.3.
[0106] (3) Granulation: The raw material shaped and classified in step (2) is mixed with the adhesive asphalt and then granulated, and the granulation size X is controlled to be 1.3 to obtain the first material.
[0107] (4) Graphitization: The first material in step (3) is subjected to high-temperature graphitization treatment in a graphitization furnace at 3200° C. The graphitization temperature is raised to 3200° C. for 35 hours, kept at a constant temperature for 45 hours, and then naturally cooled to 150° C. to obtain a second material.
[0108] (5) Coating and carbonization: The second material obtained in step (4) and asphalt with a softening point of 200°C are mixed in a mass ratio of 97:3, preheated at 300°C for 3 h, and then carbonized in a carbonization furnace at 1150°C for 48 h.
[0109] (6) Screening and demagnetization: The material obtained in step (5) is screened and demagnetized to obtain conventional process negative electrode material.
[0110] Experimental example
[0111] The negative electrode materials of each embodiment and comparative example are respectively prepared into batteries, specifically comprising:
[0112] (1) Preparation of negative electrode sheet: The negative electrode active material, conductive agent Super-P, thickener CMC, and adhesive styrene-butadiene rubber (SBR) are dissolved in deionized water at a weight ratio of 95:2:1.5:1.5 and mixed evenly to prepare negative electrode slurry. The negative electrode slurry is evenly coated on the current collector copper foil, dried, cold pressed, trimmed, cut into pieces, and slit into strips to prepare negative electrode sheets for lithium-ion batteries.
[0113] (2) Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate (LiFePO4), the conductive agent Super-P, and the adhesive polyvinylidene fluoride (PVDF) are dissolved in N-methylpyrrolidone (NMP) at a weight ratio of 8:1:1 and mixed evenly to prepare a positive electrode slurry. The positive electrode slurry is evenly coated on the current collector aluminum foil, dried, cold pressed, trimmed, cut into pieces, and slit to prepare the positive electrode sheet of the lithium-ion battery.
[0114] (3) Preparation of electrolyte: In a glove box filled with argon, carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1:1, and fully dried sodium salt of lithium hexafluorophosphate (LiPF6) was added. The concentration of the lithium salt was 1.0 mol / L, and the electrolyte was obtained after mixing evenly.
[0115] (4) A 12 μm polyethylene film (PE) was used as the separator.
[0116] (5) Preparation of lithium-ion batteries: The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in order, with the separator being located between the positive and negative electrode sheets to play an isolating role, thereby obtaining a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after drying, an electrolyte is injected, and a lithium-ion battery is obtained after vacuum packaging, standing, pre-charging, and formation processes.
[0117] (6) Preparation of three electrodes for lithium-ion soft-pack batteries:
[0118] A. Stack the above-mentioned positive electrode sheets, separators, and negative electrode sheets in order, with the separator being located between the positive and negative electrode sheets. There are 15 positive electrode sheets and 16 negative electrode sheets in total, to obtain a bare cell electrode group.
[0119] B. Soak the copper wire in hydrochloric acid solution and set aside; hot-press the bare cell electrode group, remove the tape of the hot-pressed electrode group, and start from the middle of the side of the electrode group to open a part of the electrode group (such as 16 negative electrodes, open from the 7th to the 10th); select a flat, wrinkle-free, and burr-free diaphragm for cutting. Its size is the same as the diaphragm in the bare cell electrode group, and the length is about 5 cm. Place the cut diaphragm in the center of the negative electrode sheet, and align the upper and lower widths with the original diaphragm.
[0120] C. Place the soaked copper wire on the cut diaphragm to ensure that it does not contact the negative electrode interface. The other end of the copper wire extends from the side of the pole ear, with a length of about 15 cm. Use a fine tape (green tape used to fix the pole group, with a width of 1 to 2 mm) to fix the copper wire to the upper edge of the diaphragm.
[0121] D. Put the opened half of the electrode assembly back to its original place, align the upper and lower halves of the electrode assembly, and use tape to stick and fix the electrode assembly again.
[0122] E. The copper wire drawn out from the electrode group is fixed to the outer surface of the electrode group with tape, and a layer of diaphragm is coated on the copper wire as a protective layer for the copper wire. After the assembly is completed, the copper wire is placed on one side of the soft-pack battery cell and fixed with tape. A diaphragm is used to protect the copper wire on the back of the battery cell. The diaphragm is fixed with tape and placed in the outer packaging aluminum-plastic film. The prepared electrolyte is injected into the dried battery cell. After standing, forming, and volume separation, a three-electrode battery is obtained.
[0123] F. After the battery cell is formed and placed under the cabinet, remove the protective diaphragm, extend the copper wire from the side along the aluminum-plastic shell on the upper part of the electrode group, and use a welding gun to solder the copper wire to the nickel strip with tin; the nickel strip extends 1-2 cm from the side of the battery cell, use tape to stick the nickel strip and copper wire together (except the part of the nickel strip extending outside the battery cell), and fix them to the aluminum-plastic bag on the upper part of the electrode group.
[0124] Use the charge and discharge cabinet to plate sodium on the copper wires on both sides of the positive and negative electrodes of the welded battery cells. When plating sodium on the positive reference, the positive electrode of the equipment is connected to the positive ear of the battery cell, and the negative electrode is connected to the reference electrode of the battery cell. When plating lithium on the negative reference, the positive electrode of the equipment is connected to the negative ear of the battery cell, and the negative electrode is connected to the reference electrode of the battery cell. Lithium plating process: 20μA lithium plating for 1 hour, 10μA lithium plating for 1 hour, 5μA lithium plating for 1 hour; after lithium plating, check whether the positive reference and negative reference potentials are normal: the positive reference voltage is slightly greater than the positive and negative voltages, and the positive reference minus the negative reference voltage is equal to the positive and negative voltages. That is, the three electrodes of the lithium-ion soft-pack battery are obtained.
[0125] The battery performance test is as follows:
[0126] (1) Charging test of three electrodes of lithium-ion battery: At 25°C, the charging rate is designed to transition from a small rate to a large rate from 0.5C to 10C (adjusted by 1C each time), and constant current charging is performed (the battery design voltage is an upper limit voltage of 4.1V). At the same time, the negative electrode potential is detected. Charging is stopped when the negative electrode potential is less than 0V, and then the battery is discharged at a rate of 1 / 3C at 25°C to obtain the charging rate of the three electrodes of the lithium-ion battery prepared in each embodiment.
[0127] (2) At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were fully charged at 8C and fully discharged at 1C for 20 times, and then fully charged at 8C. The negative electrode plates were then disassembled and the lithium deposition on the surface of the negative electrode plates was observed. A lithium deposition area of less than 5% on the negative electrode surface was considered to be slight lithium deposition, a lithium deposition area of 5% to 20% on the negative electrode surface was considered to be moderate lithium deposition, and a lithium deposition area of more than 20% on the negative electrode surface was considered to be severe lithium deposition.
[0128] (3) Cyclic performance test of lithium-ion batteries: At 25° C., the lithium-ion batteries prepared in the examples and comparative examples were charged at a rate of 8C and discharged at a rate of 1C, and a full charge and discharge cycle test was performed until the capacity of the lithium-ion battery decayed to 80% of the initial capacity, and the number of cycles of the lithium-ion battery was recorded.
[0129] The performance test results of the battery are shown in Table 2.
[0130] Table 2 Battery performance test results
[0131] Group 10-80% SOC charging time Lithium deposition at the interface Cycle life Comparative Example 1 12.8min Severe lithium deposition 568 weeks Example 1 6.3min No lithium deposition 1800 weeks Example 2 5.5min No lithium deposition 2000 Week Example 3 7.2min Mild lithium deposition 1500 weeks Example 4 5.9min No lithium deposition 1900 Week Example 5 6.6min Mild lithium deposition 1850 Week Example 6 6.1min No lithium deposition 1950 Week Example 7 6.3min No lithium deposition 1800 weeks Example 8 6.1min No lithium deposition 1950 Week Example 9 6.8min Mild lithium deposition 1500 weeks Example 10 6.6min Mild lithium deposition 1600 weeks Embodiment 11 6.7min Mild lithium deposition 1550 weeks Example 12 5.8min No lithium deposition 1900 Week Example 13 6.9min Mild lithium deposition 1500 weeks Embodiment 14 7.1min Mild lithium deposition 1400 weeks Embodiment 15 7.3min Mild lithium deposition 1300 weeks
[0132] As shown in Table 2, the batteries prepared from the negative electrode materials of Examples 1 to 15 of the present invention have a shorter charging time, which is within 7.5 minutes, a better interface, that is, less lithium deposition or no lithium deposition, and a better cycle performance, with a cycle life of 1300 weeks or more. The battery obtained from the negative electrode material of Comparative Example 1 has a charging time of up to 12.8 minutes, severe lithium deposition at the interface, a cycle life of 568 weeks, and poor cycle performance.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode material, characterized in that: It includes a base material and a composite coating layer coated on the surface of the base material, the base material includes a composite of graphite and hard carbon, the base material has a porous structure, the composite coating layer includes a first coating layer coated on the surface of the base material and a second coating layer coated on the surface of the first coating layer, the first coating layer includes a carbon material and a conductive agent, and the second coating layer includes a lithium-containing compound.
2. The negative electrode material according to claim 1, characterized in that The conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene and acetylene black; And / or, the lithium-containing compound includes at least one of lithium phosphate, lithium acrylate and lithium sulfonate.
3. A method for preparing a negative electrode material, characterized in that: The following steps are involved: Granulating a mixture of pretreated raw material coke and resin to obtain a first material, graphitizing the first material to obtain a second material, and pyrolyzing a mixture of the second material and alkaline solution to obtain a matrix material; The mixture of the base material, the surface modifier and the conductive agent is carbonized to form a first coating layer, and then a lithium compound solution is coated on the surface of the first coating layer, and a second coating layer is formed after drying to obtain a negative electrode material with a composite coating layer.
4. The method for preparing the negative electrode material according to claim 3, characterized in that: The invention comprises at least one of the following features (1) to (3): (1) The pretreated raw coke includes at least one of petroleum coke, needle coke and coal-based pitch coke; (2) The particle sizes D10, D50 and D90 of the pretreated raw coke satisfy the following conditions: 1.1≤(D90-D10) / D50≤1.6; (3) The pretreated raw coke is obtained by shaping and grading raw coke with a particle size D50 of 5 to 15 μm.
5. The method for preparing the negative electrode material according to claim 3, characterized in that: The method comprises at least one of the following features (1) to (6): (1) The resin comprises a phenolic resin; (2) The mass ratio of the pretreated raw coke to the resin is (85-95):(5-15); (3) the mixture of the pretreated raw coke and the resin is subjected to heat treatment and then granulated; (4) The granulation size of the first material is X=D2 / D1, wherein D2 is the particle size D50 of the first material after granulation, D1 is the particle size D50 before granulation, and X=1.2-2; (5) The temperature of the graphitization treatment is 2000-3200° C., the heating time of the graphitization treatment is 40-50 hours, and the constant temperature time is 40-50 hours; (6) After the graphitization treatment, the steel is naturally cooled to 120-155°C.
6. The method for preparing the negative electrode material according to claim 3, characterized in that: Contains at least one of the following features (1) to (4): (1) The alkali solution includes at least one of a KOH solution and a NaOH solution; (2) The mass ratio of the second material to the alkali solution is (5-8):(2-5); (3) The temperature of the pyrolysis treatment is 500 to 1000° C., and the time of the pyrolysis treatment is 1 to 4 hours; (4) The pyrolysis treatment is carried out under protective gas conditions.
7. The method for preparing the negative electrode material according to claim 3, characterized in that: The invention comprises at least one of the following features (1) to (9): (1) The surface modifier includes at least one of petroleum asphalt, coal asphalt, polymer materials, resins and biomass materials; (2) The conductive agent includes at least one of carbon black, conductive graphite, carbon fiber, carbon nanotube, graphene and acetylene black; (3) The lithium-containing compound includes at least one of lithium phosphate, lithium acrylate and lithium sulfonate; (4) In the lithium-containing compound solution, the mass percentage of the lithium-containing compound is 5% to 15%; (5) The mass ratio of the matrix material, the surface modifier, the conductive agent and the lithium-containing compound solution is (70-95):(3-10):(1-5):(1-5); (6) The temperature of the carbonization treatment is 600 to 1900° C., and the time of the carbonization treatment is 48 to 72 hours; (7) A preheating treatment is performed before the carbonization treatment, the temperature of the preheating treatment is 200 to 500° C., and the time of the preheating treatment is 5 to 8 hours; (8) The drying temperature is 100 to 200° C.; (9) After the drying, the process further includes screening and demagnetization.
8. A negative electrode sheet, characterized in that: A negative electrode material comprising the negative electrode material according to any one of claims 1 to 2, or a negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 3 to 7.
9. A battery, characterized in that: A negative electrode sheet comprising the negative electrode sheet according to claim 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
Citation Information
Cited By
High-power silicon-carbon composite material, preparation method and application thereof
CN121076099A
